Comparative Analysis of Different Technique for Detection of Noise in Restored Image (International Journal of Engineering and Computer Science, 2018)
Image restoration is the process of reconstruction or recovering an image that has been corrupted by some degradation phenomenon. Degradation may occur due to motion blur, Gaussian blur, noise and camera mismatch. In this paper corrupted image have been recovered using Modified Lucy Richardson algorithm in the presence of Gaussian blur and motion blur. The performance of this algorithm has been compared with Wiener filter, Blind deconvolution and Lucy Richardson algorithm. The performance comparison done on the based on peak signal-to-noise ratio (PSNR), Mean Square Error (MSE) and Structural Similarity Index for Measuring Image (SSIM).The result shows that Blind deconvolution Method is better than Wiener filter and Lucy Richardson algorithm